2016
DOI: 10.1038/ncomms11445
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction blocks neuropathology and motor deficits in Machado–Joseph disease mouse models through SIRT1 pathway

Abstract: Machado–Joseph disease (MJD) is a neurodegenerative disorder characterized by an abnormal expansion of the CAG triplet in the ATXN3 gene, translating into a polyglutamine tract within the ataxin-3 protein. The available treatments only ameliorate symptomatology and do not block disease progression. In this study we find that caloric restriction dramatically rescues the motor incoordination, imbalance and the associated neuropathology in transgenic MJD mice. We further show that caloric restriction rescues SIRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 48 publications
5
70
1
Order By: Relevance
“…demonstrated that this antioxidant, also known as sirtuin 1 (SIRT1) activator, improved balance and motor deficits in a MJD/SCA3 mouse model, when administered after disease onset. This study pointed SIRT1 modulation by resveratrol as a potential therapeutic target for MJD/SCA3 …”
Section: Therapeutic Strategies For Polyq Diseasesmentioning
confidence: 55%
“…demonstrated that this antioxidant, also known as sirtuin 1 (SIRT1) activator, improved balance and motor deficits in a MJD/SCA3 mouse model, when administered after disease onset. This study pointed SIRT1 modulation by resveratrol as a potential therapeutic target for MJD/SCA3 …”
Section: Therapeutic Strategies For Polyq Diseasesmentioning
confidence: 55%
“…86 Sirtuins are considered to have an important role in mediating the beneficial effects of CR on longevity. 87,88 Similar with CR, SIRT1 overexpression is helpful to extend the life span and decrease the disease syndromes of neurodegenerative diseases. CR induced the expressions of sirtuins, such as SIRT1, SIRT3, SIRT5, and SIRT7.…”
Section: Caloric Restrictionmentioning
confidence: 99%
“…For scheduled feeding, the access to food was restricted to 6 h per day during the dark cycle, and mice were sacrificed after a week on scheduled feeding at the end of a fasting period. Long-term caloric restriction has beneficial effects on aging and neurodegenerative phenotypes (29, 30), and previous studies have implicated both mTOR inhibition and SIRT1 activation in these phenomena (29, 31-33). Consistent with these reports, we observed that scheduled feeding decreased phosphorylated mTOR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…mHTT aggregates accumulate with aging, and HD is a progressive disease that in the majority of patients only manifests in adulthood. While caloric restriction can slow aging in a large variety of animal models (54) and upregulate key transcription factors such as SIRT1 that are beneficial in different neurodegenerative conditions including HD (29, 31, 32), such an intervention is not advisable for human patients, since HD already leads to a significant reduction in body weight (55) which may be exacerbated by further calorie reduction. However, we show here that scheduled feeding is sufficient to upregulate SIRT1 expression and activate the mTOR pathway in a mouse model of HD.…”
Section: Discussionmentioning
confidence: 99%